Distinct neural representations of different linguistic components following sign language learning - Yael Coldham; Neta Haluts; Eden Elbaz; Tamar Ben-David; Nell Racabi; Shachar Gal; Michal Bernstein-Eliav; Naama Friedmann; Ido Tavor (Communications Biology)
Abstract Learning a new language is a process everyone undergoes at least once. However, studying the neural mechanisms behind first-time language learning is a challenging task. Here we aim to explore the functional alterations following learning Israeli Sign Language, a visuo-spatial rather than an auditory-based language. Specifically, we investigate how phonological, lexical, and sentence-level components of the language system differ in their neural representations. In this within-participant design, hearing individuals naïve to sign languages (n = 79) performed an fMRI task requiring the processing of different linguistic components, before and after attending an Israeli Sign Language course. A learning-induced increase in activation was detected in various brain regions in task contrasts related to all sign language linguistic components. Activation patterns while processing different linguistic components post-learning were spatially distinct, suggesting a unique neural representation for each component. Moreover, post-learning activation maps successfully predicted learning retention six months later, associating neural and performance measures.